Adenosine A2B receptor stimulates angiogenesis by inducing VEGF and eNOS in human microvascular endothelial cells. (November 2015) - Du, Xiaolong; Ou, Xuehai; Song, Tao; Zhang, Wentao; Cong, Fei; Zhang, Shihui; Xiong, Yongmin
Angiogenesis is critical to wound repair due to its role in providing oxygen and nutrients that are required to support the growth and function of reparative cells in damaged tissues. Adenosine receptors are claimed to be of paramount importance in driving wound angiogenesis by inducing VEGF. However, the underlying mechanisms for the regulation of adenosine receptors in VEGF as well as eNOS remain poorly understood. In the present study, we found that adenosine and the non-selective adenosine receptor agonists (NECA) induced tube formation in HMEC-1 in a dose-dependent manner. Adenosine or NECA (10 µmol/L) significantly augmented the number and length of the segments in comparison with the control. Simultaneously, VEGF and eNOS were significantly upregulated following the administration of 10 µmol/L NECA, while they were suppressed after A2B AR genetic silencing and pharmacological inhibition by MRS1754. In addition, VEGF expression and eNOS bioavailability elimination significantly reduced the formation of capillary-like structures. Furthermore, the activation of A2B AR by NECA significantly increased the intracellular cAMP levels and concomitant CREB phosphorylation, eventually leading to the production of VEGF in HMEC-1. However, the activated PKA-CREB pathway seemed to be invalidated in the induction of eNOS. Moreover, we found that the elicited PI3K/AKT signaling in response to the induction of NECA assisted in regulating eNOS but failed to impact on VEGF generation. In conclusion, the A2B AR activation-driven angiogenesis via cAMP-PKA-CREB mediated VEGF production and PI3K/AKT-dependent upregulation of eNOS in HMEC-1.